A Computational Exploration of the Color Gamut of Nanoscale Hollow Scalene Ellipsoids of Ag and Au - Kealley, Cat; Cortie, M. (Springer, 2010)
Hollow, nanoscale, scalene ellipsoids of Ag or Au provide an exceedingly tunable localized surfaceplasmon resonance. Here, we use numerical simulations to determine the limits of the color space that would be possible from colloidal suspensions of these particles and show that their color gamut will exceed that possible with nanorods, nanoshells, or nanorice. The important parametersare composition, thickness of the shell, and shape of the particle, in that order. The sensitivity of colors to geometry is optimized for an aspect ratio of between 0.3 and 0.5 and was reduced for thinner shells. Shells of Ag will have much wider and more vibrant gamut than those of Au. These findings indicate that hollow scalene ellipsoids could be used as versatile pigments in materials or display systemsthat exploit plasmon resonance to produce color.